Investment of endowment funds in the higher educations: best practices, performances and issues - Ayuniyyah, Qurroh; Haneef, Mohamed Aslam; Mustaffa Kamil, Nazrol Kamil (Fakulti Pengajian Islam, UKM, 2014)
Purpose – The role of endowment funds in higher education across countries in last decades has been important as one of the major funding sources to finance academic activities. Many well-known universities in the world have implemented different strategies for investment management of endowment funds in order to achieve their long-term objectives. The main purposes of this paper are to perform an analysis of conventional endowment funds of higher education and to articulate some benchmarks or best practices related to the financial management of endowment funds. Besides, the paper identifies some unique issues or challenges faced by endowment funds. Design/Methodology/Approach – The study evaluates the current practices of conventional endowment funds management of universities based on secondary sources of information, including published reports, journal papers, articles and books. Findings – The model of endowment fund investment differs from one university to another. The paper reviews the current practices and strategies of the largest universities’ endowment fund investment activities. Originality/value – By providing a general review in the conventional endowment funds of higher education, it is expected to have valuable input, which delivers lessons to be learned for contemporary waqf institutions and Islamic third sector. However, the main issue is comparability, where the majority of conventional endowment fund is invested in form of financial assets, while waqf is mostly in the form of real assets, but there is similarity in nature between endowment and waqf funds. Keywords Investment, Endowment Funds, Higher Education Paper type General review